A Correlation Between Solutions of Uncertain Fractional Forward Difference Equations and Their Paths - Srivastava, Hari Mohan; Mohammed, Pshtiwan Othman (Frontiers in Physics, 2020)
We consider the comparison theorems for the fractional forward h-difference equations in the context of discrete fractional calculus. Moreover, we consider the existence and uniqueness theorem for the uncertain fractional forward h-difference equations. After that the relations between the solutions for the uncertain fractional forward h-difference equations with symmetrical uncertain variables and their α-paths are established and verified using the comparison theorems and existence and uniqueness theorem. Finally, two examples are provided to illustrate the relationship between the solutions.